The UI/UX Design with Design Thinking Method for The University Complaint Website - Milda Puspita, Silvy; Apriyanti, Narti (Information Technology International Journal, 2023)
One system that can be used to manage and resolve complaints within the university is the complaint system. The Complaint System that has been provided at UPN "Veteran" East Java seems not to be optimal because the service response is slow. The design of the UI/UX complaint website "Wadulan Ing UPNVJT" was carried out using the design thinking method in this study, which focuses on potential users so that they can produce websites that meet user criteria. The purpose of designing this website is to produce complaints system designs and features that suit user needs by rearranging problems and adopting ideas through a direct approach to users. The results of the study are a complaint system prototype in the form of a display for users and admins based on exploring needs and searching for the core problems experienced by users. The approach taken is to use a questionnaire with a total of 18 samples at the empathize stage and involve 5 respondents at the testing stage. The conclusion obtained from the test results using usability testing is that the website that has been designed meets the user criteria with a percentage result of 94% which can be categorized as very good.